The Properties of Lion Roars and Electron Dynamics in Mirror Mode Waves Observed by the Magnetospheric MultiScale Mission. Issue 1 (3rd January 2018) - Breuillard, H.; Le Contel, O.; Chust, T.; Berthomier, M.; Retino, A.; Turner, D. L.; Nakamura, R.; Baumjohann, W.; Cozzani, G.; Catapano, F.; Alexandrova, A.; Mirioni, L.; et al.
Abstract: Mirror mode waves are ubiquitous in the Earth's magnetosheath, in particular behind the quasi‐perpendicular shock. Embedded in these nonlinear structures, intense lion roars are often observed. Lion roars are characterized by whistler wave packets at a frequency ∼100 Hz, which are thought to be generated in the magnetic field minima. In this study, we make use of the high time resolution instruments on board the Magnetospheric MultiScale mission to investigate these waves and the associated electron dynamics in the quasi‐perpendicular magnetosheath on 22 January 2016. We show that despite a core electron parallel anisotropy, lion roars can be generated locally in the range 0.05–0.2 f ce by the perpendicular anisotropy of electrons in a particular energy range. We also show that intense lion roars can be observed up to higher frequencies due to the sharp nonlinear peaks of the signal, which appear as sharp spikes in the dynamic spectra. As a result, a high sampling rate is needed to estimate correctly their amplitude, and the latter might have been underestimated in previous studies using lower time resolution instruments. We also present for the first‐time 3‐D high time resolution electron velocity distribution functions in mirror modes. We demonstrate that the dynamics of electrons trapped in the mirror mode structures are consistent with the Kivelson and Southwood (1996) model. However, these electrons can also interact with the embedded lion roars: first signatures of electron quasi‐linear pitch angle diffusion and possible signatures of nonlinear interaction with high‐amplitude wave packets are presented. These processes can lead to electron untrapping from mirror modes. Key Points: Intense lion roars are observed in mirror modes by high time resolution instruments on board Magnetospheric MultiScale mission Nonlinear lion roars are observed up to 0.4 f ce due to their high amplitude, which may have been underestimated in previous studies Possible signatures of linear and nonlinear resonant interaction between lion roars and electrons, which can be untrapped from mirror modes